A study on vehicle equivalency factor for expressway and two-lane highway in North Luzon - Acacio, Alan Anthony Lorenzo (Animo Repository, 2005)
Vehicle equivalency factors are used to account for the prevailing conditions of mixed traffic in the highway into that of ideal capacity. In particular, the presence of heavy vehicles and other low performance vehicles greatly affects the operations of the roadway and its capacity. This heavy vehicle equivalent factor appears as fHV in the U.S. Highway Capacity Manual (USHCM) and uses the passenger-car equivalents (PCEs) to individually establish the impact of trucks ET, buses EB and recreational vehicles ERV on traffic operations. In Philippine conditions, other types of vehicles present in the local traffic stream specifically jeepneys, mini buses, tricycles, and indigenous transport modes like kuliglig which were assumed to affect traffic capacities and operations along rural highways due to their low performance operations were analyzed. Methods for determining PCEs were reviewed and driver-determined equivalence (headway method) for expressway and multiple linear regressions model for two-lane, two-way highways were applied. The average PCE values are estimated to be 1.04 for small/medium sized vehicles and 1.60 for large sized vehicles. PCE of passenger-jeepneys are observed to be similar to passenger-cars in the expressway. Light Vehicle Equivalents (LVEs) were used instead of Passenger Car Equivalents (PCEs) in moderate to steep grade terrain in Marcos highway. The LVE estimates for heavy truck vehicles and bus vehicles are 11.6 and 8.8 respectively. PCE for bus vehicle and heavy truck vehicle are 1.6 and 1.2 respectively for level grade terrain at Manila North Road (MNR). Percentile speed PCE resulted to unstable and insignificant results due to trucks and low performance vehicles inability to operate at higher speeds. The study was able to confirm that, under local conditions, increasing the percentage of large and low performance vehicles in the traffic stream adversely affects the capacity of the highways.